1998
DOI: 10.2337/diacare.21.12.2123
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Impaired Left Ventricular Wall Motion in the Diabetic Heart Without Coronary Artery Disease

Abstract: Our findings suggest that impairment of myocardial FFA metabolism rather than small vessel abnormalities in the myocardium is responsible for modest left ventricular dysfunction in patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
0
12
1
1
Order By: Relevance
“…In addition, other studies have shown changes of myocardial blood flow without alterations of myocardial oxygen consumption. Congruent with our findings of the dobutamine response, diabetic patients do not exhibit lactate production dur-ing atrial pacing [40]. In summary, although vascular structural and functional changes may be related to glycemic control, and some authors have connected these entities [32••,41], the balance of the data do not support vascular changes as the primary contributor to diabetic heart disease.…”
Section: Diabetic Vascular Diseasecontrasting
confidence: 77%
“…In addition, other studies have shown changes of myocardial blood flow without alterations of myocardial oxygen consumption. Congruent with our findings of the dobutamine response, diabetic patients do not exhibit lactate production dur-ing atrial pacing [40]. In summary, although vascular structural and functional changes may be related to glycemic control, and some authors have connected these entities [32••,41], the balance of the data do not support vascular changes as the primary contributor to diabetic heart disease.…”
Section: Diabetic Vascular Diseasecontrasting
confidence: 77%
“…Various studies confirmed the occurrence of LV dysfunction in DM subjects; however the influence of DM on RV function is considered controversial and inconsistent. 4,5,27,28 Nevertheless it is unexpected for all these structural and functional changes to affect only the LV, whereas RV remains normal. In this study, we were able to show a significant impairment in RV function as well as LV function by using novel sensitive TDI-indices.…”
Section: Discussionmentioning
confidence: 99%
“…® DM has been known to be an independent risk for congestive heart failure and depressed LV function, 1-3 which appears to be independent of coronary artery disease or other comorbid conditions. [3][4][5][6][7][8] There has been controversy, however, as to whether the occurrence of LV dysfunction in DM patients could be related to microvascular coronary abnormalities 9,10 or undiagnosed epicardial coronary artery disease. Thus, the abnormal flow in the small vessels may be pathogenetically involved in the cause of DM cardiomyopathy; however, decrease in RV function or isolated chronic right heart failure secondary to coronary artery disease does not exist.…”
Section: Discussionmentioning
confidence: 99%
“…
D iabetes mellitus (DM) has been found to be an independent risk for congestive heart failure and depressed left ventricular (LV) function 1,2 and appears to be independent of other cardiovascular comorbid conditions. [2][3][4][5][6][7] The cause of diabetes cardiomyopathy is not known. We hypothesized that a direct negative effect of DM on the myocardial structure independent of coronary artery disease, should also involve right ventricular (RV) function.
…”
mentioning
confidence: 99%